The autonomic nervous system dysregulation in response to orthostatic stress in children with neurocardiogenic syncope - (:unkn) unknown (CAMBRIDGE UNIV PRESS, 2010)
Neurocardiogenic syncope is a common disorder, which is considered as a benign condition. However, sudden loss of conscience and muscle tone causes anxiety among the family members due to its similarity to sudden death. Autonomic nervous system dysregulation is thought to be responsible in the aetiology. Heart rate variability is used for assessment of autonomic nervous system. We evaluated 24 children between 6 and 18 years (mean plus or minus standard deviation is equal to 12.5 plus or minus 3.28, with neurocardiogenic syncope and 10 healthy controls, mean plus or minus standard deviation is equal to 12.48 plus or minus 3.27) by using 24 hour Ho her monitorisation and head-up tilt test. Heart rate variability analysis was performed using the Holter recordings obtained both during head-up tilt test and throughout the day. Our results revealed that, there is no significant difference between the study and the control groups in terms of the mean heart rate and all indices of the heart rate variability (p > 0.05). However, during the first 5 minutes of the head-up tilt test, standard deviation of all RR intervals and root mean square of successive differences were significantly lower in the syncope group compared with the control group, 42.17 plus or minus 12.56 versus 60.10 plus or minus 33.10 and 21.26 plus or minus 8.87 versus 36.80 plus or minus 31.03; p-values 0.02 and 0.03, respectively. In conclusion; autonomic functions in children with neurocardiogenic syncope are similar to healthy children. However, sympathetic hyperactivation occurs during the early phase of orthostatic stress in children with neurocardiogenic syncope comparing to healthy controls. Parasympathetic innervation is not sufficient in compensation of this sympathetic hyperactivation. Management strategy in neurocardiogenic syncope should be based on these pathophysiologic mechanisms.
Keywords: Syncope; vasovagal; neurocardiogenic; head-up tilt test; heart rate variability; autonomic functions; HEART-RATE-VARIABILITY; NEURALLY-MEDIATED SYNCOPE; VASOVAGAL SYNCOPE; UP TILT; UNEXPLAINED SYNCOPE; FAMILIAL OCCURRENCE; DOMAIN ANALYSES; VAGAL CONTROL; TIME; HERITABILITY